Modernising Social Work and the Ethics of Care - Gabrielle Meagher (Social Work and Society)
Recent attempts to 'modernise' social work have emphasised the importance of collaboration, partnership, and participation with individual users of services and the wider community. However, technical-rational aspects of managerialism have proved dominant. Managerialist approaches to social service administration and delivery threaten important dimensions of social work; specifically its caring and democratic-transformative dimensions. However, social work theorists have only recently begun to re-engage with ideas of care. We argue that closer attention to feminist debates about the ethics of care can make a significant contribution to not only rehabilitating the ideal of care for social work but also to moving forward the modernisation agenda itself. We develop a feminist critique of managerialism, and argue that the discourse of the ethics of care offers useful ways of framing arguments to counter some damaging impacts of managerial reforms.